Evaluación de hemerotecas electrónicas: Resultados de un estudio de usuarios realizado en la Hemeroteca Electrónica de la Facultad de Ciencias de la Información de la Universidad Complutense. - Arquero Avilés, Rosario; García-ochoa Roldán, Mª Luisa (Revista General de Información y Documentación, 2004)
The sudy was performed on the electronic newspapers library of the faculty of information science. This study describes the formation and developement of the electronic library. Particular attention was paid to describe in detail who the various users were and their degree of satisfaction in using the electronic library. Finally, the results of this survey are used in the planning of short, medium and long periods of time.
Keywords: Electronic Newspapers Library; University Libraries; Users Study; Plan; Design and Evaluation of Information and Documentation; Faculty of Information Science of Complutense University